APPLICATION OF THE 5R METHOD IN WASTE MANAGEMENT ON Jl. STARBAN, MEDAN POLONIA - Nanda, Meutia; Elvina, Elvina; Anggraini, Riri; Lauchan, Agil Maritho; Purba, Sumiarti (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Garbage is one of the problems that occurs in the city of Medan. Based on 2021 National Waste Management Information System (SIPSN) statistics, Medan City produces up to 2000 tons of waste per day, of which only around 30 tons can be processed, thereby increasing the burden on the environment. This data shows that the amount of waste produced has exceeded the daily projection in Medan City of 1,326.37 tons. Handling the remaining waste at the Final Processing Site (TPA) also adds to the complexity of this waste problem. The 5R waste management technique is an alternative waste management approach that involves community involvement. Objective: To find out the application of the 5R method in waste management on Jl. Starban, Medan Polonia. Method: Using a combination of practice and counseling, this research is descriptive qualitative in nature. The Accidental Sample approach was used in this research. This research was attended by 30 housewives as research subjects. Observations, surveys, and documentation are used to collect data. Research Results: It was found that before conducting counseling and joint practice with the community of Jl. Starban, Medan Polonia, the level of public knowledge is only 25%. After counseling and joint practice, the community has high self-awareness regarding waste management using the 5R method. This is proven by the results of the final questionnaire measuring the level of knowledge which reached 100% from 30 respondents. Suggestion: The community can participate in dealing with waste problems through waste management using the 5R method.